Bone stress injuries in athletics (track and field) championships: findings from a prospective injury surveillance conducted across 24 international championships with 29,147 registered athletes - Hoenig, T.; Tenforde, A. S.; Hollander, K.; Junge, A.; Branco, P.; Vinther, A.; Edouard, P. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background Athletics (track and field) athletes are prone to develop bone stress injuries (BSIs) but epidemiological data on BSIs from top-level sports events are scarce.